A Health Education Perspective in Exploring the Emotional Disorder of Shellfish Workers in Their Socio-Occupational Context - María Paz Diéguez; Rodríguez-García, María Dolores (Journal of Knowledge Management Practice, 2025)
Women shellfish gatherers work in a context where gender and other social determinants interact in a complex social structure. The objective is to explore the emotions faced by women shellfish gatherers in their socio-occupational experiences. This was done through focus group and thematic analysis. The roles, conditions, situations, emotions and emotional associations that these women usually experience are exposed. Common emotions that, without being classified as a disorder, can affect emotional well-being. Group health education is crucial to help them recognise, manage emotions and enable them to care for emotional well-being in their context.
Keywords: knowledge management; shellfish gatherers on foot; emotions; emotional distress; health promotion; health education